2017
DOI: 10.1097/qai.0000000000001312
|View full text |Cite
|
Sign up to set email alerts
|

Project Engage: Snowball Sampling and Direct Recruitment to Identify and Link Hard-to-Reach HIV-Infected Persons Who Are Out of Care

Abstract: The alternative approaches presented were effective at locating marginalized HIV-positive persons who are OOC for linkage and retention. The SNR approach was most successful at identifying alters with serious social challenges and gaps in needed medical/ancillary services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Target populations were primarily PWH who had challenges being engaged in HIV care. Examples include PWH with a history of incarceration (n=8) [11, 14-17, 19-21], with recent/new HIV diagnosis (n=5) [10, 14, 18, 20-21], with comorbid conditions such as substance use and mental health problems (n=4) [10, 13, 19, 22], and those who were veterans (n=1) [23], women (n=1) [8], or racial minorities (n=1) [10].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Target populations were primarily PWH who had challenges being engaged in HIV care. Examples include PWH with a history of incarceration (n=8) [11, 14-17, 19-21], with recent/new HIV diagnosis (n=5) [10, 14, 18, 20-21], with comorbid conditions such as substance use and mental health problems (n=4) [10, 13, 19, 22], and those who were veterans (n=1) [23], women (n=1) [8], or racial minorities (n=1) [10].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen out of the 20 studies (85%) [5, 8-9, 11-12, 14-21, 23-26] reported any positive associations between patient navigation and any HIV care continuum outcome. Except for the three studies that did not provide statistical tests [14, 16, 20], all of the positive associations were statistically significant.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, study participants were asked to inform their friends about the research opportunity. These activities represented established best practices for recruitment of hidden and hard to reach populations (Wohl et al., 2017).…”
Section: Methodsmentioning
confidence: 99%